Ruptura amorosa y su incidencia en la autoestima en un adulto de 25 años del Cantón Quevedo - Loor Loor, Erika Eloisa (2023)
The present case study has as its theme love breakup and its impact on self-esteem in a 25-year-old adult from the Quevedo canton. Its objective is to propose activities that contribute to the improvement of the adult's self-esteem. A breakup is the end of a romantic relationship and can be a painful and challenging process. Self-esteem is fundamental to our emotional health and our ability to face life's challenges. In this research, instruments were carried out such as: direct observation, semi-structured interview, clinical history, psychometric tests, as well as the Beck depression inventory and the Barreto general self-esteem questionnaire. A therapeutic scheme focused on Cognitive Behavioral Therapy was developed, using techniques: psychoeducation, cognitive restructuring, alternative interpretations, written ventilation and self-listing. In which the adult expresses himself better and to develop the activities and thus obtain positive results and thus be able to resume his activities. A diagnosis was obtained according to the ICD 10 criteria, the patient meets the criteria of Mild Depressive Episode with coding (F 32.0). During the investigation, a love breakup has a strong impact on the adult's emotional and cognitive level